Chemical Vapor Deposition of High‐Optical‐Quality Large‐Area Monolayer Janus Transition Metal Dichalcogenides (Adv. Mater. 38/2022). Issue 38 (23rd September 2022) - Gan, Ziyang; Paradisanos, Ioannis; Estrada‐Real, Ana; Picker, Julian; Najafidehaghani, Emad; Davies, Francis; Neumann, Christof; Robert, Cedric; Wiecha, Peter; Watanabe, Kenji; Taniguchi, Takashi; Marie, Xavier; et al.
Abstract : Janus Monolayers In article number 2205226, Bernhard Urbaszek, Antony George, Andrey Turchanin, and co‐workers present a new method to grow large‐scale and high‐structural‐quality SeMoS Janus monolayers on Au substrates. Their high optical quality is demonstrated by optical and magneto‐optical measurements which reveal the strong exciton‐phonon coupling and enable an exciton g‐factor of −3.3 to be obtained. Cover art by Shahab Mohebi Fard.